Pulses Consumption and its Determinants among Rural Households: A Micro-level Evidences from Central Zone of Uttar Pradesh (Indian Journal of Extension Education, 2017)
The present study was undertaken with the aim to analyze the status of pulses consumption in rural household representing different socio-economic strata in central Uttar Pradesh state of India. A total of two hundred farm households were sampled for the study using stratified random sampling technique from five villages namely Barapur, Kuitkheda, Muhamadpur, Sariapur and Bewan of purposively selected district of Kanpur Dehat. Size of the landholding owned by the households was the criterion for the stratification of the households. Personal interviews using a pretested interview schedule along with 24-hour dietary recall method were used to collect primary data from the active male and the female of the households together about consumption of pulses in household and was later compared to the Recommended Dietary Allowances (RDA) to assess the adequacy status. The findings showed that pigeon pea and chickpea were cultivated by all the sampled households (100%) belonging to large land holding category followed by about 82 per cent and 72 per cent in medium land holding category and about 94 and 64 per cent in small land holding categories, respectively. The per cent area under black gram was observed to increase with decrease in land holding category. In addition, mung bean was also observed to be most preferred among small land holding category that was grown on an average 0.22 acres of land for every sampled mungbean growers which was about 23 per cent of the gross area under pulse crops among the same category. Among the pulse products consumed, the frequency of consumption of chickpea products was found to be highest among all the categories of households with a large variation in ranging from 61 to 208 times per year. However, with respect to recommended per capita intake of pulses there were significant variations for medium farmers (-39.13%), small (-39.98%) and landless categories (-77.56%) of farmers except for the large farmers for whom the gap was found to be only -2.63%. The average family education score of selected farm households showed a decreasing trend within the land holding categories with the reduction in the landholding size.